From Partnership to Ownership: Reflections on a Community-University Research Partnership - Mercier J; Sanders J; Takie ME; Kerr L; MacNicol D; Hall H (SAGE Publications, 2025)
This article presents an example of a community-university research partnership which was focused on issues of sustainability and long-term community benefit throughout. It documents a five-year relationship between an Aotearoa New Zealand based university and a number of youth and community organisations. The project aimed to co-develop tools and resources that would support youth and social service practitioners to maintain effective helping relationships with vulnerable young people. It also aimed to develop a kaitiaki (caretaker) group of community partners at the project conclusion so that they could continue to share the resources with others. The article documents reflections from both community and research partners, outlining relational processes of finding our way, negotiating and renegotiating, and shifting ownership that supported community partners to see themselves as kaitiaki of the research and the resources. The processes highlight learning that may be valuable for others working in long-term partnerships where post-project sustainability is prioritised.
Keywords: partnership; community development; community-university partnership; long-term research partnership; community based qualitative research